Konsep Fitrah dalam Psikologi Islam - Muhammad Faiz Al Afify (TSAQAFAH, 2018)
Human beings and the complexity they have will never run out to be studied and discussed. So, one of interesting topics of psychology to discuss is concept of ‘fitrah’. The most essential identity of human beings is ‘fitrah’. This issue is more interesting if it is viewed through two perspectives: modern psychology and Islamic psychology. Both kinds of psychology have denied each other. The basis of modern psychology which is separated from element of divinity, makes the conception of ‘fitrah’ dichotomist-secularistic, this is the opposite of Islamic psychology. According to Islam, human beings consist of bodies and rûḥ. Obviously, the two aspects have a specific purpose. At least, Allah states that the purpose of human creation consists of two things, worshipping Him and becoming His khalîfah on this earth. So, the paradigm of Islamic psychology is absolutely related to the element of divinity. God remains the highest subject and influences the paradigm of Islamic psychology which is being tawḥîdiy. For various natural structures they have and the purpose of their creation, human beings are considered to have goodness potency and could do good things. However, external influences still allow them to do evil doings or bad things. This paper discusses this concept of ‘fitrah’ using Islam as a paradigm. The author tries to explain the concept of man as a creature created by fitrah, its physical and psychological structure, and the purpose of human creation and its implications for the psychology paradigm of Islam.